Technologıcal and economıc dırectıons of organızatıon and management of publıc and prıvate cooperatıon (Економіка і регіон/ Economics and region, 2024)
In the article, the essence of the formation of public-private sector cooperation was explained, the directions and compliance of the innovative activity of cooperation with the law, cooperation mechanism and factors were determined. At the same time, the directions that characterize the technological and institutional nature of public-private cooperation were investigated, defined and systematized. The formation and regular improvement of the mechanism for the implementation of infrastructure projects aimed at the restoration and reconstruction of the territories of Karabagh and Eastern Zangezur economic regions was considered as a priority of cooperation. In the new economic conditions, the implementation of the economic policy of independent Azerbaijan within the framework of large-scale reforms has determined the preservation of macroeconomic stability in our country, the diversification of the economy, the acceleration of the balanced development of the non-oil sector and regions, and the further improvement of the social welfare of the population. Strengthening of state support for entrepreneurial activity has led to the creation of free competition and a favorable investment environment for the development of the private sector. In addition to these, the dynamic progress observed in all areas has created conditions for the successful implementation of the works defined within the framework of the four State Programs on socio-economic development of regions in our Republic. Research of existing experiments shows that innovative activities in the organization and management of effective activities of public and private cooperation, centers for joint use of scientific and technical equipment, experimental – test bureaus, structures, experimental objects, business incubators, etc. such areas of activity should be formed and their joint use should be ensured. At the same time, in the direction of this activity, the process of improving information and communication technologies, creation and systematization of national and global information resources , the development of the mechanism for their effective use is a joint effective function of public-private cooperation in the field of using the experience available in the world in this field it is one of the priority directions for the organization, management and implementation of the organization.
Keywords: innovation; public; private; partnership; economic; technological; liberated territories; program; strategy